Penggunaan Pronomina Persona dalam Takarir (Caption) Instagram @Jokowi dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Yeni Aryanti; Hilda Hilaliyah; Ira Pratiwi Ramdayana (Universitas Indraprasta PGRI, 2022)
This study aims to analyze the use of personal pronouns in @Jokowi's Instagram caption and its implications for learning Bahasa, besides that the author also hopes that readers can understand the language and using pronouns according to Indonesian rules. The method used in this study is a qualitative descriptive method with content analysis techniques. Based on the results of research and analysis, it is known that the use of personal pronouns reached 127 findings from a total of 51 uploads studied, 7 uploads contained no use of personal pronouns. The findings of the first-person singular pronouns were 67 (53%), first-person singular pronouns 38 (30%), second-person singular pronouns 4 (3%) and plural 0 (0%), and the last is third-person pronouns. singular as many as 5 (4%) and plural as many as 13 (10%) findings. Keywords: Pronouns, Persona Pronouns, Indonesian Language Learning, Instagram, Jokowi.